IMPLEMENTATION OF OUTDOOR LEARNING METHOD IN TEACHING POETRY WRITING TEXTS TO 10TH GRADE STUDENTS AT NU KAPLONGAN HIGH SCHOOL - Lutfi, Muhammad Irpan (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2023)
This research was motivated by the low ability and interest of students in learning to write poetry in class X SMA NU Kaplongan. The objectives of this study were 1) to determine the effectiveness of the outdoor learning method in learning to write poetry in class X SMA NU Kaplongan; 2) to describe the process of learning to write poetry using the outdoor learning method in learning to write poetry in class X SMA NU Kaplongan. The research method used in this study is an experimental study. The method of collecting data in this study was by collecting data from observations and tests (pretest and posttest). Based on statistical results using the normality test, homogeneity test and two independent samples t test, a tcount of 4.151 and a ttable of 1.677 is obtained. So tcount (4.151) > ttable (1.677). This shows that Hο is rejected and Hı is accepted. Thus, it can be stated that the application of the outdoor learning method is effective in learning to write poetry in class X SMA NU Kaplongan in the 2022/2023 academic years.